2009
DOI: 10.1109/tns.2009.2023444
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Multiplexing Effects in Multi-Pinhole Small Animal SPECT: A Simulation Study

Abstract: Our goal is to study the trade-off between image degradation and improved detection efficiency and resolution from allowing multiplexing in multi-pinhole (MPH) SPECT, and to determine the optimal pinhole number for MPH design. We used an analytical 3D MPH projector and two digitized phantoms: the mouse whole body (MOBY) phantom and a hot sphere phantom to generate noise-free and noisy projections, simulating pinhole collimators fitted with pre-studied pinhole patterns. We performed three schemes to achieve dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 16 publications
4
48
0
Order By: Relevance
“…Although determination of optimal aperture sizes in MPH is usually task-dependent and is beyond the scope of this study, different sizes of pinholes for other applications can be tailored and applied by using other aperture plates. Studies from authors and other researchers have shown that multiplexing leads to image artifacts and should be avoided or kept to minimal [17,25]. However, complete blockage of the multiplexing, while still fully utilizing the whole detector, is difficult to achieve without the use of physical septa for a circular FOV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although determination of optimal aperture sizes in MPH is usually task-dependent and is beyond the scope of this study, different sizes of pinholes for other applications can be tailored and applied by using other aperture plates. Studies from authors and other researchers have shown that multiplexing leads to image artifacts and should be avoided or kept to minimal [17,25]. However, complete blockage of the multiplexing, while still fully utilizing the whole detector, is difficult to achieve without the use of physical septa for a circular FOV.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive degree of multiplexing has been recognized to degrade the reconstructed image quality and provides inferior bias and noise trade-off [17,25]. When applying the same collimator length for mice to rats in MPH imaging, the higher degree of multiplexing may cause excessive image artifacts in the reconstructed images.…”
Section: Effects Of Multiplexingmentioning
confidence: 99%
See 2 more Smart Citations
“…These are commonly combined with simulation tools accounting for all physical aspects involved in the image acquisition process and characteristics of the imaging system to generate a simulated dataset that closely mimic clinical and experimental studies. The known features of computational models and simulated datasets provide precise information enabling to evaluate the impact of physical degrading factors inherent to the imaging process, [131][132][133][134][135] assess different design concepts and performance of medical imaging systems, [136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] and advance the development and validation of new image segmentation, [151][152][153][154][155] registration, 156-161 reconstruction, [162][163][164][165][166][167] and processing techniques. [168][169][170][171][172][173][174][175] Likewise, the Digimouse and MOBY models served as optically heterogeneous virtual subjects for light propagation calculations to assess the impact of various parameters involved in optical molecular imaging techniques [176]…”
Section: C Medical Imaging Physicsmentioning
confidence: 99%